Biosynthesis of the anti‐lipid‐microdomain sphingoid base 4, 14‐sphingadiene by the ceramide desaturase FADS3. Issue 2 (8th January 2020) - Jojima, Keisuke; Edagawa, Mai; Sawai, Megumi; Ohno, Yusuke; Kihara, Akio
Abstract: Sphingolipids are multifunctional lipids. Among the sphingolipid‐component sphingoid bases, 4, 14‐sphingadiene (SPD) is unique such that it has a cis double bond with a bent structure. Although SPD was discovered half a century ago, its tissue distribution, biosynthesis, and degradation remain poorly understood. Here, we established a specific and quantitative method for SPD measurement and found that SPD exists in a wide range of mammalian tissues. SPD was especially abundant in kidney, where the amount of SPD was 2/3 of sphingosine, the most abundant sphingoid base in mammals. Although SPD is metabolized to ceramides and SPD 1‐phosphate with almost the same efficiency as sphingosine, it is less susceptible to degradation by a cleavage reaction, at least in vitro. We identified the fatty acid desaturase family protein FADS3 as a ceramide desaturase that produces SPD ceramides by desaturating ceramides containing sphingosine. SPD sphingolipids were preferentially localized outside lipid microdomains, suggesting that SPD has different functions compared to other sphingoid bases in the formation of lipid microdomains. In summary, we revealed the biosynthesis and degradation pathways of SPD and its characteristic membrane localization. Our findings contribute to the elucidation of the molecular mechanism underlying the generation of sphingolipid diversity.